Gut microbiota and atopic dermatitis in children: a scoping review - Yue Liu; Xiaofan Du; Shujie Zhai; Xiaodong Tang; Cuiling Liu; Weihong Li (BMC, 2022)
Abstract Background Gut microbiota plays an important role in the development of atopic dermatitis (AD). We aimed to elucidate research trends in gut microbiota and AD in children, to provide evidence and insights to the clinical prevention and treatment of AD in children. Methods A scoping literature review on the studies of gut microbiota and AD were conducted. Two authors independently searched Pubmed et al. databases for studies focused on gut microbiota and AD in children up to January 15, 2022. The literatures were screened and analyzed by two reviewers. Results A total of 44 reports were finally included and analyzed. Current researches have indicated that abnormal human microecology is closely associated with AD, and the disturbance of intestinal microbiota plays an important role in the occurrence and development of AD. Probiotics can correct the microbiota disorder, have the functions of regulating immunity, antioxidant, and help to restore the microecological homeostasis. However, there is still a lack of high-quality research reports on the efficacy and safety of probiotics in the prevention and treatment of AD in children. Conclusions The changes of gut microbiota are essential to the development of AD in children, which may be an effective target for the prevention and treatment of AD. Future studies with larger sample size and rigorous design are needed to elucidate the effects and safety of probiotics in AD.